151k views
6 votes
Anyone know the answer to this ​

Anyone know the answer to this ​-example-1
User Donel
by
5.3k points

2 Answers

10 votes

Answer:

x = 112

Explanation:

The common denominator is 56 because 8*7 is 56


-(7*7*x)/(8*7) -(5*x)/(56)+(8*x)/(56) = - 92 \\-(49*x)/(56) -(5*x)/(56)+(8*x)/(56) = - 92 \\(-46*x)/(56)=-92

Multiply both sides by 56

-46*x = -92 * 56

-46*x = -5152

Divide by - 46

x = -5152/-46

x = 112

User Kenny Rullo
by
5.4k points
2 votes

Answer:

x=112

Explanation:

First, let's get all of the fractions to a common denominator.

Based on the numbers given (8,56, and 7), let's make all of the denominators be 56

for
(-7)/(8) x, multiply the numerator and denominator by 7.


(-7x)/(8)×
(7)/(7)=
(-49)/(56) x

we can leave
(-5)/(56)x as it is

and for
(1)/(7) x, we cam multiply the numerator and denominator by 8


(1x)/(7)×
(8)/(8)=
(8x)/(56)

Here's the equation now:


(-49x)/(56)-
(5x)/(56)+
(8x)/(56)=-92

now simlify the fractions

numerators:

-49x-5x+8x=-46x

here's the fraction now:


(-46x)/(56)=-92

We can simplify the fraction by 2 so it's
(-23x)/(28)


(-23x)/(28)=-92

now multiply both sides by
(28)/(-23), which is the reciprocal of
(-23)/(28) (to isolate the variable)


(28)/(-23)×
(-23x)/(28)=-92×
(28)/(-23)


(-92*28)/(-23)

x=112

Hope this helps!

User Axel Scheithauer
by
5.4k points